2006
DOI: 10.1158/0008-5472.can-05-1292
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Is Constitutively Produced by Human Peritoneal Mesothelial Cells and Enhances Adhesion, Migration, and Invasion of Ovarian Cancer Cells

Abstract: Lysophosphatidic acid (LPA) is both a potential marker and a therapeutic target for ovarian cancer. It is critical to identify the sources of elevated LPA levels in ascites and blood of patients with ovarian cancer. We show here that human peritoneal mesothelial cells constitutively produce LPA, which accounts for a significant portion of the chemotactic activity of the conditioned medium from peritoneal mesothelial cells to ovarian cancer cells. Both production of LPA by peritoneal mesothelial cells and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
158
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(167 citation statements)
references
References 46 publications
8
158
1
Order By: Relevance
“…We tested whether cPLA 2 and/or iPLA 2 were similarly involved in LPA-induced migration of ID8 cells as those human EOC cells (2,10,11,13,24). A general inhibitor (AACOCF3) for both cPLA 2 and iPLA 2 almost completely blocked LPA (1 μmol/L)-induced ID8 cell migration, suggesting that one or both of these enzymes are involved in the process (Fig.…”
Section: Lpamentioning
confidence: 99%
See 1 more Smart Citation
“…We tested whether cPLA 2 and/or iPLA 2 were similarly involved in LPA-induced migration of ID8 cells as those human EOC cells (2,10,11,13,24). A general inhibitor (AACOCF3) for both cPLA 2 and iPLA 2 almost completely blocked LPA (1 μmol/L)-induced ID8 cell migration, suggesting that one or both of these enzymes are involved in the process (Fig.…”
Section: Lpamentioning
confidence: 99%
“…We and others have shown that LPA stimulates the migration and invasion of ovarian cancer cells (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Although most, if not all, of these studies were conducted in established ovarian cancer cell lines, we have recently conducted LPA-and S1P-induced cell migration and invasion experiments in primary EOC and nonmalignant human ovarian surface epithelial cells (11,23).…”
Section: Introductionmentioning
confidence: 99%
“…The high autonomous proliferation rate of the metastatic ovarian cancer cells, their ability to develop alternative means of survival, as well as the contributions of inflammatory cells present in malignant effusions are believed to be responsible for the pluoripotent nature of these malignant effusions (2)(3)(4)(5). Ovarian cancer cells and peritoneal mesothelial cells constitutively produce bioactive lipids and cytokines that further promote motogenesis and mitogenesis of ovarian cancer cells in both autocrine and paracrine fashion (6)(7)(8)(9). The autocrine secretion of cytokines, peptide growth factors, as well as proteolytic enzymes by malignant cells not only contributes to ascites accumulation but also enhances their survival and dissemination (1,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…LPA has been reported to induce cellular proliferation in primary ovarian carcinoma cells, prostate cancer cell lines, amnionic cells, chondrocytes, and so on [3][4][5]. LPA also induces cellular migration and invasion in fibroblasts or some cancer cells, such as ovarian cancer cells [6,7]. In terms of cell surface receptors for LPA, certain type of G-protein coupled receptor (GPCR) such as LPA 1 , LPA 2 , and LPA 3 have been reported [8,9].…”
Section: Introductionmentioning
confidence: 99%